Angkringan names in Semarang: A linguistic landscape study - Maghfiroh, Nurul; Suhandano, Suhandano; Firmonasari, Aprillia (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
The article reveals the linguistic landscape study of angkringan names in Semarang City. It covers language preference, language inference, and language preservation on signages. Researchers collected 140 pictures of angkringan signages from 10 sub-districts of Semarang. Observation and interviews are also conducted to obtain comprehensive linguistic landscape data. Qualitative analysis indicates that there are two naming patterns: monolingual and bilingual. The monolingual analysis identifies that the most preferred language code is Javanese, followed by Indonesian, English, and Sanskrit. Meanwhile, in the bilingual pattern, the dominant language combination used is Indonesian-Javanese, followed by Javanese-English, Javanese-Indonesian, Javanese-Dutch, Sanskrit-English, and Sundanese-English. Meanwhile, angkringan names draw references from diverse sources, including people, places, slogans, hopes, objects, menus, mythological figures, and numbers. In terms of language preservation, this study identified that Javanese is predominantly used on angkringan signages for small-scale entrepreneurs as an identity, while big-scale entrepreneurs focus on attracting customers. This implies that economic factors are one of the driving forces behind the use of Javanese on signs.